Doomed from the start: what is the value of selecting a future dominant design? - Tegarden, Linda F.; Hatfield, Donald E.; Echols, Ann E. (Strategic Management Journal, 1999)
This study investigates how important it is for a firm to select what turns out to be a dominant design in a technology-driven industry. Using the personal computer industry as a case study, this research shows that firms are not doomed when their entry design choices turn out to be ‘wrong.’ For early entrants, we found that switching to the dominant design is associated with increased chances of survival and market share. Contrary to our expectations, we found that even later entrants that switched to the dominant design also enjoyed higher survival rates and greater market position. Copyright © 1999 John Wiley & Sons, Ltd.